Achilles Tendon Xanthoma and Cholestanol Revealing Cerebrotendinous Xanthomatosis: A New Case Report - Ahmed Ghassem, Mohamed; Mounach, Aziza; H Djossou, Julien; Toufik, Hamza; El Ouardi, Najlae; Achemlal, Lahsen; Bezza, Ahmed (Case Reports in Rheumatology, 2021)
Cerebrotendinous xanthomatosis (CTX) is an autosomal recessive lipid storage disease rarely reported in Africa. Therefore, we report a Moroccan first case report of CTX. A 20-year-old woman was presented in our department for bilateral swelling of the posterior aspect of ankles and the anterior aspect knees with gait disturbances evolving since the age of 7. The patient was the first child of consanguineous marriage. She had bilateral cataracts and developmental delay. Laboratory findings revealed that the plasma cholestanol level was remarkably elevated, and plasma and urine bile alcohol levels were elevated. MRI of ankles showed a bilateral diffuse thickening of the Achilles tendon with hypointense in T1 and heterogeneous hypersignal in T2 with spots in hypersignal in T1 and T2. Brain MRI revealed bilateral and symmetrical T2 hypersignal of dentate nuclei, without white matter signal alterations or cerebral or cerebellar atrophy. A biopsy obtained of the Achilles swelling with a histological study showed an aspect of tendon xanthoma. Hence, the diagnosis of CTX was made. MRI, especially brain MRI, plays an important role in the diagnosis of CTX.